A study of motivation factors among participants in aerobic dance programme at a fitness centre / Rinawati Zulkiffli - Zulkiffli, Rinawati (2002)
Physical activity is important for maintaining a healthful lifestyle. Most sport and exercise participants are activated by intrinsic and extrinsic motivation, but may differ in their perception. This study was conducted to know and identify the motivational factors among participants for their involvement in an aerobic dance programme at TCGF, Kompleks PKNS Shah Alam. Fifty-two subjects aged 20 - 49 years old from TCGF were voluntarily selected for this study. A self-administered questionnaire divided into demography, background of participation, intrinsic motivation and extrinsic motivation, were used for collecting data. Out of 52 subjects, 45 were females and seven were males. The subjects in this study comprised 80.8% Malays, 11.5% Chinese and 7.7% Indians. All the data were analyzed by using SPSS and presented as frequency and percentage. From the result it was found that, the subjects were motivated to participate aerobic dance programme in factors; intrinsic motivation and extrinsic motivation. Most of the subjects agreed to the factors from intrinsic motivation (weight concern, health and fitness, enjoyment/interest, release tension personal goal achievement, psychological concern, self-esteem and competence/challenge) motivated them to participate in aerobic dance programme. The factors from extrinsic motivation also motivate their participation including get support, reward, team orientation, class environment, physical appearance and social interaction. The study therefore concluded that the subjects in the present study were motivated by intrinsic and extrinsic motivation. Thus, the subjects must follow methods of motivating in order to stay motivated to participate in aerobic dance programme. However, further research is required to determine others factor that contribute to the participation of the participants in aerobic dance programme.